Making Your First Year a Success : a Classroom Survival Guide for Middle and High School Teachers. - Wyatt, Robert L., III (SAGE Publications, 2007)
This second edition helps secondary teachers incorporate technology and differentiation into instruction, connect lesson planning and standards, deal with stress, and nurture themselves emotionally and physically.